Posterior Urethral Valves (PUV): Experience of Follow up Over 7 years (Bangladesh Journal of Urology, 2020)
Objectives: Posterior urethral vale is one of the major common congenital obstructive urethral lesions in male children. Endoscopic fulguration with observation is the treatment of choice for posterior urethral valves (PUV). This prospective study was carried out to assess the outcome of endoscopic fulguration of posterior urethral valves based upon the clinical, radiological and laboratory findings.Methods : The study started in Bangabandhu Sheikh Mujib Medical University Hospital in October 2004 on 50 male children with posterior urethral valves who were treated with endoscopic fulguration and came for routine follow up. Diagnosis was established by voiding cystourethrogram (VCUG) and confirmed by urethrocystoscopic findings.. The patients came for follow up after valve ablation at three months interval up to 1 year, and at six months interval for seven years.Results: Mean age of the patients was 2 years ranging from 1 to 12 years old. At diagnosis mean serum creatinine level ± SD was 90.4±44.8 μmol /litre and it decreased to 58.3±11.4μmol/litre at the end of 7 years follow up. Hydronephrotic changes decreased from decreased from 84% to 2%. Proteinuria decreased from 38% to 4%.Urinary tract infections decreased from 58% to 8% at the end of last follow up.Conclusion: In this study patients improved dramatically following fulguration of posterior urethral valves. But these patients need regular follow up because some of these patients may develop ESRD in the long run.Bangladesh Journal of Urology, Vol. 15, No. 2, July 2012 p.40-43